Embedded System of DNA Exon Predictor using Hidden Markov Model - Habibi Husain, Arifin; Ahmad Nasir, Che Rosli; R. Badishah, Ahmad, Assoc. Prof. Dr.; Suhartati, Agoos, Dr. Ir; Ferrianto, Gazali, M. Sc., Ir.; Endang Djuana, ST. M. Eng.; Md. Mostadjur, Rahman; Safarin, Samsudin (Universit Sains Malaysia, 2010)
National Research and Innovation Competition (NRIC) 2010, 26th - 28th May 2010 was held at Dewan Utama Pelajar, USM Main Campus, Penang, Malaysia. Organized by the Student Representative Council of Universiti Sains Malaysia.